'Drugs and Relationships Don't Work': Children's and Young People's Views of Substance Use and Intimate Relationships. (21st November 2013) - Galvani, Sarah
Abstract : Responding effectively to children and young people's (CYP's) needs in relation to the overlapping issues of parental substance use (alcohol and other drugs) and domestic abuse requires an understanding of their perspectives and experiences. This study set out to explore the views of CYP on the impact of substance use on violent and abusive behaviours within intimate relationships in order to inform practice and policy development. Fourteen young people attended focus groups at three different specialist substance use support services for families in England. The results showed clear ambivalence about alcohol use in particular and its impact on violent and abusive behaviours. They did not blame substances for subsequent violent or abusive behaviour overall, however, the quantities and type of substances used were considered key to such behaviour. Most importantly, the CYP reported that getting help with substance problems does not automatically improve relationships, indeed, there are situations when pressure to change substance use can make relationships worse. The implications for social care practice are discussed. Copyright © 2013 John Wiley & Sons, Ltd. 'Clear ambivalence about alcohol use in particular and its impact on violent and abusive behaviours' Key Practitioner Messages: CYP need clear and factual messages about the relationship between substance use and violent and abusive behaviours, particularly messages about the quantity and types of substance. This requires practitioners to be confident in their knowledge and have accurate and age‐appropriate information to give to CYP. Practitioners need to ask CYP about their experiences of the impact of substance use on the family and the relationships within it. It is possible that relationships were abusive and/or the parenting was not 'good enough' before the substance use and will not improve in its absence. The CYP highlighted how relationships face different pressures at different times in the process of changing substance use behaviour. CYP need to be supported and consulted throughout. 'Relationships face different pressures at different times in the process of changing substance use behaviour'